Nonpharmacological Treatment for Supporting Social Participation of Adults with Depression - Supaluck Phadsri; Rieko Shioji; Atsuko Tanimura; Jeerawit Jaknissai; Sopida Apichai; Tippawan Sookruay (Occupational Therapy International)
Background. Social withdrawal is predominantly seen among adults with depression. However, a dearth of reviews exists that explore nonpharmacological treatments, especially occupational therapy (OT) interventions and their effect in promoting social participation. The aim of this research was to review what intervention programs are conducted to support the social participation of adults with depression and their effectiveness. Method. A systematic review was performed wherein relevant articles were searched in PubMed, CINAHL, Wiley Online Library, PsycINFO, and OTseeker databases and AJOT, BJOT, SJOT, and OTMH journals. Only English articles published from January 2010 to December 2018, which tackled intervention for adults aged 20–60 years with depression, were considered. Ten out of 918 studies met the screening criteria. Result. Among the ten studies, the effective intervention programs were categorized as either occupation-based intervention (OBI) or cognitive behavioral therapy-based intervention (CBT-BI). These programs sought the following outcomes: behavioral change in social participation (n=4), reduction of depression or depressive symptoms (n=13), life satisfaction (n=4), and quality of life (QoL) (n=1). Studies showed moderate (n=3) to strong (n=7) level of certainty, whereas they also revealed high to unclear (n=3) and low (n=7) risk of bias. Conclusion. Both OBI such as animal-assisted therapy and CBT-BI such as behavioral change program and health education have a strong level of certainty and low risk of bias in promoting social participation by supporting positive behavioral change and reducing depressive symptoms. Furthermore, the sport and exercise program of OBI was popular in encouraging participation and engagement with other people. Other programs were suggested for combined interventions to support social participation, life satisfaction, and QoL.